Determinant Analysis of Gender Inequality in Human Development in Indonesia - Zalukhu, Rika Surianto; Collyn, Daniel (Budapest International Research and Critics University, 2021)
The purpose of this research is to examine the impact of poverty, unemployment, economic growth, elderly population, and the average time female education period on gender inequality in human development in Indonesia. The dependent variable is gender inequality. The independent variables are poverty, unemployment, economic growth, elderly population, and female education period. This research was conducted in 34 provinces in Indonesia with an observation period of 2019. The type of data used is secondary data. Data collection was done through online access on Badan Pusat Statistik website. Data analysis method used was multiple regression analysis. The result shown that the number of elderly population and economic growth partially give positive and significant impact on gender inequality in human development in Indonesia. Poverty, unemployment, and the female education period partially give negative and insignificant impact on gender inequality in human development in Indonesia.